ผลของการฝึกยิงประตูบาสเกตบอลควบคู่กับการเสริมด้วยเมดิซินบอล และการฝึกจินตภาพที่มีต่อความสามารถในการกระโดดยิงประตูบาสเกตบอล - เสาวลักษณ์ เหล่าเลิศรัตนา (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
To study effects of basketball shooting training with the supplementary training by medicine ball and imagery training on basketball jumpshot ability. Subjects were 60 female students of Sueksasongkor Bangkruay school, aged between 14-18 years old. The subject were tested for basketball jump shot ability and then were divided into four groups with 15 subjects in each group by matched group method. the first group was trained for a supplementary training by medicine ball and basketball shooting training, the second group was trained by imagery training and basketball shooting training, the third group was trained by medicine ball, imagery training and basketball shooting training and the fourth group was trained by only basketball shooting training. Each group was trained for 8 weeks with 3 days a week. They were tested for basketball jump shot ability after 4 weeks and 8 weeks of training period. Data were then analyzed in term of means, standard deviations, one-way analysis of variance, one-way analysis of variance with repeated measurement and Tukey method. The results were found that 1 After the experiment for 8 weeks, basketball jump shot ability of all four groups were significantly higher than before the experiment at the .05 level. 2. After the experiment for 8 weeks, basketball jump shot ability of three experimental groups were significantly higher than of the control group at the .05 level. 3. After the experiment for 8 weeks, there were no any significant difference in basketball jump shot ability among three experimental groups.